2015
DOI: 10.1097/jnr.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Living Under the Constant Threat of Ebola

Abstract: Living under the constant threat of Ebola is experienced as distressing in the physical, social, and psychological realms. In the future, prompt treatment and nursing care are recommended to minimize deaths and to reduce the widespread terror, anxiety, ostracism, and stigmatization that affected individuals and families face. Furthermore, it is recommended that the resilience of survivors and caregivers be increased to facilitate their better coping with the rampant antisocial overtones that they are likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Early, continuous, and professional psychological interventions can prevent physical and mental harm. Patients endure stress during an epidemic and may experience physical and mental reactions ( Matua and Van der Wal, 2015 ; Mohammed et al., 2015 ). The stressors of the patients noted in this study were the disease itself, the treatment regimens in quarantine, and concerns regarding family health, resulting in changes in mood, diet, sleep, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Early, continuous, and professional psychological interventions can prevent physical and mental harm. Patients endure stress during an epidemic and may experience physical and mental reactions ( Matua and Van der Wal, 2015 ; Mohammed et al., 2015 ). The stressors of the patients noted in this study were the disease itself, the treatment regimens in quarantine, and concerns regarding family health, resulting in changes in mood, diet, sleep, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, healthcare workers displaying physical symptoms may face a sense of fear, stigmatisation and ostracism from co-workers, which may exacerbate the psychological pain. 24 26 …”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that close to a quarter (24.9%) of survivors exhibited a possible case of anxiety which is slightly higher than those reported by Nanyonga et al [ 31 ] and Mohamed et al [ 44 ] in Kenema, Eastern Sierra Leone. Although studies from East Africa [ 45 47 ] and in Guinea [ 28 ], Nigeria [ 48 ] Liberia [ 49 ] and within Sierra Leone [ 30 , 50 52 ] using quantitative and qualitative research designs have reported that psychological harm is common among Ebola survivors, it has failed to assess anxiety among Ebola survivors specifically, and this makes comparison among studies to be difficult. For instance, a study by Ji et al in Sierra Leone, anxiety was part of positive symptom distress index (PSDI) that was used to evaluate psychological distress among Ebola survivors, medical personnel and logistics workers [ 51 ].…”
Section: Discussionmentioning
confidence: 99%